Factors of economic sustainability of the food industry enterprises - Pidgirnyj, Igor; Bozhok, Natalia (My University, 2014)
The current operating conditions of commercial enterprises are characterized by constant dependence on all subjects of general infrastructure. Enterprises are constantly working with internal and external environment, they try to strengthen its position in the market and weaken the position of competitors.In such circumstances, the activities of the company can not protect against adverse shocks. Therefore, there is the issue of economic security (stability) under the negative influence of the environment, the ability to quick remove threats and adapt to conditions that are favorable to the business, using its capabilities.
Keywords: food industry enterprises; commercial enterprises; economic sustainability; комерційні підприємства; економічна стійкість; підприємства харчової промисловості; предприятия пищевой промышленности; коммерческие предприятия; экономическая устойчивость; кафедра ділової іноземної мови та міжнародної комунікації